Tribals and the Indian constitution : functioning of fifth schedule in the state of Orissa - Behura, N. K. (Rawat Publications, 2017)
India harbours multiple ethnic groups who have distinct socio-cultural identities. It is one of the nation-states in the world, which has provided elaborate preferential arrangements for the tribals. The tribal communities in India are at different levels of socio-economic development. In view of the deep-rooted historic reasons, which have caused the backwardness of these communities, the Indian Union as well as states are committed to ensure the implementation of the constitutional provisions for their development. The book, which is based on an empirical study, has extensively reviewed the impact of various legislations and regulations enacted for tribal development in Orissa in the past. Besides presenting an anthropological understanding of tribal development along with a brief account of tribal development programmes being implemented in the country, it also explains the state of vulnerable tribal population in Orissa.In a nutshell, the book discusses issues such as indebtedness, excise policy, land tenure system, role of welfare agencies etc., which are directly concerned with the tribal people."